Comparison of scour caused by hollow and solid jets of water - Doddiah, Doddiah, author; Albertson, Maurice L., advisor; Rollins, Ralph L., committee member; Harris, David V., committee member; Guard, Harris T., committee member; Weber, Louis R., committee member (Colorado State University. Libraries, 1949)
To view the abstract, please see the full text of the document.
Covers not scanned.
Keywords: Hydraulics